Use of Cleavable Coordinating Rings as Protective Groups in the Synthesis of a Rotaxane with an Axis that Incorporates More Chelating Groups Than Threaded Macrocycles. Issue 38 (9th August 2013) - Joosten, Antoine; Trolez, Yann; Heitz, Valérie; Sauvage, Jean‐Pierre
Abstract A new methodology allowing preparation of a linear "unsaturated" [3]rotaxane consisting of an axis incorporating more coordination sites than threaded rings was developed. It was based on the preliminary synthesis of a "saturated" [5]rotaxane consisting of a four‐chelating site axis threaded through four macrocyclic components, two of them being cleavable rings incorporating a lactone function and the two others being "secure" non‐cleavable rings. The stoppering reaction was based on click chemistry. Subsequently, cleavage and removal of the two lactone‐containing macrocycles from the [5]rotaxane in basic medium afforded the desired "unsaturated" [3]rotaxane in quantitative yield.